Resorbable versus titanium osteosynthesis devices in bilateral sagittal split ramus osteotomy of the mandible: the results of a two centre randomised clinical study with an eight-year follow-up - Stockmann, Philipp Hubertus Andreas; Böhm, Hartmut; Driemel, Oliver; Mühling, Joachim; Pistner, Hans (Journal of cranio-maxillofacial surgery, 2010)
Background - This study was conducted to compare the long-term clinical outcome of patients with jaw disproportion who had had fixation with resorbable polylactic acid containing positioning screws with those who had had titanium positioning screws in bilateral sagittal split ramus osteotomy of the mandible (BSSO). - Patients and methods - Sixty-six patients with isolated mandibular jaw disproportion were included and divided randomly into two treatment groups (resorbable and titanium). Patients were followed for 8 years postoperatively using a standardised protocol. Material-specific complications, functional problems and clinical findings within the former operation field were documented. Treatment stability was determined by occlusion criteria. - Results - Thirty-four patients (54%) were followed until the end of the study. No significant differences were observed in the outcomes of patients in the two groups related to the materials used for osteosynthesis or the long-term treatment stability. During the study, no foreign body reactions were observed. - Conclusion - This study showed that resorbable and titanium positioning screws were equally effective as fixation devices in sagittal split osteotomy. Complete resorption of the resorbable screws could not be verified because of the absence of histological examination, however, the use of resorbable positioning screws can be considered as an alternative osteosynthesis material to conventional titanium osteosynthesis devices in sagittal split osteotomy.
Gesehen am 25.08.2023